Effect of Provisional Cements on Shear Bond Strength of Porcelain Laminate Veneers - Altintas, Subutay Han; Tak, Onjen; Secilmis, Asli; Usumez, Aslihan (European Journal of Dentistry, 2011)
Objectives: The purpose of this study was to evaluate the effect of three provisional cements and two cleaning techniques on the final bond strength of porcelain laminate veneers. Methods: The occlusal third of the crowns of forty molar teeth were sectioned and embedded in autopolymerizing acrylic resin. Dentin surfaces were polished and specimens were randomly divided into four groups (n=10). Provisional restorations were fabricated and two provisional restorations were cemented onto each tooth. Restorations were fixed with one of three different provisional cements: eugenol-free provisional cement (Cavex), calcium hydroxide (Dycal), and light-cured provisional cement (Tempond Clear). Provisional restorations were removed with either a dental explorer and air-water spray, or a cleaning bur (Opticlean). In the control group, provisional restorations were not used on the surfaces of specimens. IPS Empress 2 ceramic discs were luted with a dual-cured resin cement (Panavia F). Shear bond strength was measured using a universal testing machine. Data were statistically analyzed by ANOVA, Tukey’s HSD and Dunnett tests. Surfaces were examined by scanning electronic microscopy. Results: Significant differences were found between the control group and both the light-cured provisional cement groups and the eugenol-free provisional cement-cleaning bur group (P<.05). Groups that had received light-cured provisional cement showed the lowest bond strength values. Conclusions: Selection of the provisional cement is an important factor in the ultimate bond strength of the final restoration. Calcium hydroxide provisional cement and cleaning with a dental explorer are advisable. (Eur J Dent 2011;5:373-379)
Keywords: Provisional cement; Porcelain laminate veneer; Surface cleaning techniques